PROFITABILITY ANALYSIS OF THE ADOPTION OF VALUE ADDITION TECHNOLOGIES BY WOMEN RICE PROCESSORS IN BENUE AND KOGI STATES, NIGERIA - Adejo, E.G.; Adejo, P.E.; Ajibade Y.E.; Onoja M.N. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
This study examined the profitability of the adoption of value addition technologies by women rice processors in Benue and Kogi States, Nigeria. Multi stage sampling procedure was used to select 358 women rice processors for the study. Data were collected using structured questionnaire and analysed using descriptive statistics, chi- square, mean score from likert scale and gross margin. The result on Table 1 showed women rice processors capabilities on rice improved milling technology (=2.23), cleaning and polishing rice value operation (=2.42), rice destoning (=2.34) , improved drying value addition technology(=2.14), sorting, grading and certification rice value operations (=2.03), packaging(=2.26) and storage (=2.25). On the other hand, processors in Kogi state showed their capabilities on rice improved milling (=2.05), cleaning and polishing (=2.09), destoning (=2.02), packaging (=2.06) and storage (=2.06). and have access to labour, storage, processing equipment, preservative skills, Information on market for rice value added product and good sources of paddy with the mean score of 2.29, 2.03, 2.14, 2.10, 2.09 and 2.35 respectively. However, chi- square test on both states processors showed that improved milling, Improved drying, Packaging, Product branding & labeling and Storage were significant at 5%. The study found out that rice processing is profitable in the study areas with returns per naira invested in indigenous, modern and both methods of rice processing are N1.10, N1.24 and N1.17 respectively. Women rice processors in Benue and Kogi States are highly capable of adding value to their rice through most of the value addition technologies available except in few cases. The study therefore recommends that both public and private agencies should make productive resources for rice value addition accessible to women processors as this will accelerate the rate of adoption of modern improved technologies.